2007
DOI: 10.1002/pmic.200600215
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of de‐etiolated rice seedlings upon exposure to light

Abstract: Two-week-old dark-grown rice seedlings were de-etiolated upon exposure to light. A comparison of 2-DE protein profiles between the dark-grown control and the rice seedlings illuminated respectively for 6, 12 and 24 h revealed 52 differentially expressed CBB-stained spots. Of these changed spots, the identity of 51 protein spots was determined by MALDI-TOF MS. Of these identified proteins, 13 proteins were related to light reactions of photosynthesis, photosynthetic carbon assimilation and chlorophyll biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…As expected, in our study 25 membrane proteins were identified and quantified (Table I); to our knowledge, few gel-based proteomics studies have identified so many membrane proteins. For example, we identified POR, which is abundant in etiolated seedlings but has never been identified in similar experiments using 2-DE methods (3,4). These results indicate that our newly developed MS E -based label-free method is robust, highly reproducible, and sensitive and thus is ideally suited to proteomics studies of this type.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…As expected, in our study 25 membrane proteins were identified and quantified (Table I); to our knowledge, few gel-based proteomics studies have identified so many membrane proteins. For example, we identified POR, which is abundant in etiolated seedlings but has never been identified in similar experiments using 2-DE methods (3,4). These results indicate that our newly developed MS E -based label-free method is robust, highly reproducible, and sensitive and thus is ideally suited to proteomics studies of this type.…”
Section: Discussionmentioning
confidence: 65%
“…Although many proteomics investigations have been done on lightregulated proteins in C 3 plants during seedling de-etiolation, particularly in rice and Arabidopsis (3,4), few such studies have been done in C 4 plants. Maize, which is quite distinct from Arabidopsis and rice, is a prototypical C 4 plant that exhibits classical Kranz leaf anatomy during development (34,35).…”
mentioning
confidence: 99%
See 3 more Smart Citations